Analysis methods to assess the competitiveness of enterprises - Assylbekova, Nazgul (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This paper analyzes the existing methods for assessing the competitiveness ofenterprises. In the comparative analysis of methods are determined the disadvantagesand feasibility of using each method. The author confirmed that at this time thereis no generally accepted evaluation system to assess the competitiveness of enterprises. The author to expediently and efficiently determine the level of competitiveness of an enterprise offers a method entitled “Assessment of the competitiveness of industrial products”, developed by K. Nurmagambetov.